2013
DOI: 10.1108/17561371311294810
|View full text |Cite
|
Sign up to set email alerts
|

A typology of food security in developing countries

Abstract: Journal articleIFPRI3; ISI; CRP2DSGD; EPTD; PIMPRCGIAR Research Program on Policies, Institutions, and Markets (PIM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 6 publications
1
34
0
Order By: Relevance
“…Availability connotes physical presence of food in adequate amount; accessibility implies efficient purchasing power at all times; utilization reflects the demand for sufficient quantity and quality of food intake; and sustainability refers to the adequacy of food at all times. A number of food security indicators at the micro-level have been identified in the literature (Lokosang et al 2011;Pangaribowo et al 2013;Obayelu 2013;Yu and You 2013). Some of these indicators include per capita food consumption (such as per capita nutrient intakes of calorie, protein, and fat), per capita expenditure on food, dietary diversity score/food consumption score, coping strategy index, share of dietary intake, food insecurity access scale (self-report/assessment), and anthropometry measures among others.…”
mentioning
confidence: 99%
“…Availability connotes physical presence of food in adequate amount; accessibility implies efficient purchasing power at all times; utilization reflects the demand for sufficient quantity and quality of food intake; and sustainability refers to the adequacy of food at all times. A number of food security indicators at the micro-level have been identified in the literature (Lokosang et al 2011;Pangaribowo et al 2013;Obayelu 2013;Yu and You 2013). Some of these indicators include per capita food consumption (such as per capita nutrient intakes of calorie, protein, and fat), per capita expenditure on food, dietary diversity score/food consumption score, coping strategy index, share of dietary intake, food insecurity access scale (self-report/assessment), and anthropometry measures among others.…”
mentioning
confidence: 99%
“…Food security of a nation significantly gets affects due to variation in agricultural production. Agriculture is a crucial factor to sustain food security as it can at least feed the population ever in adverse economy [32,33]. Nevertheless, in the era of globalization, food security may not be defined by agricultural production only since food security is a multidimensional, multi-processing and multiple interacting component of an economy [19,30].…”
Section: Food Security Affecting Factorsmentioning
confidence: 99%
“…There are several factors that plays a significant role to sustain food security at individual/households/national/global level. Food security is significantly associated with age, sex, occupation, employment, vegetarian and non-vegetarian diet, poverty, per capita income, income inequalities, demand of food-grains, rapid population growth, fluctuation in food-grains and oil prices, poor market accessibility, low irrigation facilities, application of fertilizer, credit accessibility, cost of cultivation, application of traditional technologies in cultivation, literacy of farmers, declining land productivity and soil quality, decline in arable land due to urbanization and industrialization, diminishing ground water availability due to over exploitation of water, geographical location, government policies, government expenditure on agriculture and rural development, public spending on R&D, natural resource management and environmental protection policies, trade policies, and climate change [1,2,5,6,[8][9][10][11]27,[32][33][34][35][36][37][38][39][40][41][42][43][44][45]. As high income inequalities increase people's involvement in illegal activities outside the market which contribute political and social instability.…”
Section: Food Security Affecting Factorsmentioning
confidence: 99%
“…The example of Lebanon reflects this lack of consensus. Three different national assessments conducted by IFPRI have found that Lebanon, as a whole, is subject to moderate food and nutrition insecurity (Breisinger et al 2010;Yu et al 2010;Ahmed et al 2013). It is worth noting, however, that these assessments were conducted at the national level, and were performed before the onset of the Syrian Crisis and resulting inflows of significant Syrian refugee populations into Lebanon.…”
Section: The Example Of Lebanon: Varying Food and Nutrition Security mentioning
confidence: 99%